2017
DOI: 10.32598/sija.13.10.360
|View full text |Cite
|
Sign up to set email alerts
|

Structural Equation Modeling a Study on the Effect of Religious Orientation on Psychological Well-Being With Respect to the Mediating Role of Death Anxiety and Self- Compassion in the Elderly Man of Kermanshah in 2017

Abstract: 1. Objectives lder adults face several health and well-being issues [1, 2]. Psychological well-being depends on a variety of factors, including spiritual commitment and religiosity [3-O 5]. Religiosity can improve mental well-being by reducing Death Anxiety (DA). Religion manages the human fear of death by the promise of immortality [6, 7]. Self-compassion is a mediating variable between religion and well-being. It is a recently developed structure that has created a new means of understanding and promoting hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…This conclusion is based on the findings of the study by Bakhshi et al . [ 18 ] Varaee et al .,[ 19 ] and Aghababaei et al . [ 17 ] According to the idea of fear management, death awareness creates high anxiety, inhibits adaptive psychological function, leads to psychological difficulties, and has a negative impact on well-being, since death anxiety conflicts with the evolutionary drive, which is for survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion is based on the findings of the study by Bakhshi et al . [ 18 ] Varaee et al .,[ 19 ] and Aghababaei et al . [ 17 ] According to the idea of fear management, death awareness creates high anxiety, inhibits adaptive psychological function, leads to psychological difficulties, and has a negative impact on well-being, since death anxiety conflicts with the evolutionary drive, which is for survival.…”
Section: Discussionmentioning
confidence: 99%
“…Several research have found a relationship between death anxiety and psychological well-being. [ 17 18 19 ]…”
Section: Introductionmentioning
confidence: 99%
“…Addressing death anxiety in the elderly population is imperative (13) because the elderly can be prone to death anxiety and psychological disorders due to the conditions their families impose on them, the inabilities due to increased age, and their care needs not being met. Thus, attention to death anxiety in this age group can increase their abilities and improve their performance in all aspects of their lives (14).…”
Section: Introductionmentioning
confidence: 99%